COMPETENCIES CONCERNING MATHEMATICS KNOWLEDGE, TEACHER PREPARATION, AND CLASSROOM MANAGEMENT, OF PRIMARY SCHOOL TEACHERS UNDER BANGKOK EDUCATION OFFICE - อารีเอื้อ บุญชัย; สุภวาลย์ พรสิน; โสขุมา กฤษณะ; ตัสโต ภัทรพร; ลือสมัย อภิชาติ; สุวรรณเสน อรพรรณ; คงเจริญ ธนวรรณ (Academic Journal Phranakhon Rajabhat University, 2018)
The purposes of this research were to (1) investigate competencies concerning mathematics knowledge, teacher preparation, and classroom management, of primary school teachers who teach mathematics under Bangkok Education Office, and (2) compare competencies concerning the aforementioned aspects of these teachers, who were classified by personal information, namely gender, age group, rank, educational qualifications, field of study, school teaching experience, mathematics teaching experience in primary schools. The population of primary school teachers under Bangkok Education Office in the entire 18 schools was 14,158. The sample derived through multi-stage sampling was 230 of them. Questionnaires were distributed to the sample by mail, and 138 copies were returned. This made the response rate 60 percent. The research instrument was a questionnaire. The Cronbach’s alpha coefficients were greater than 0.885 in all individual aspects. The statistics used for data analysis were percentage, mean, standard deviation, ANOVA, and LSD. The findings were as follows: 1. The vast majority of the respondents, accounting for 89.9 percent, were female. 39.1 of the respondents were aged between 31 and 40, and 40.6 percent completed bachelor degrees as their highest educational qualifications. Most of the respondents, representing 73.2 percent held degrees not related to mathematics. Moreover, 60.9 percent, 36.2 percent, and 74.6 percent of them attended mathematics training relating to knowledge, teacher preparation, and classroom management respectively. 2. Most of the respondents had mathematics knowledge competency at the mean score of 3.82, and its standard deviation was 0.704. Meanwhile, the mean scores of teacher preparation competency, and classroom management competency were 3.87 and 4.06 respectively. Their standard deviations of the former and latter were 0.628 and 0.589 respectively. 3. The mathematics knowledge competency and teacher preparation competency of the respondents who had less than 5 years of mathematics teaching experience were different from those of the respondents who had 5-10 years, at a significance level of .05